Academic Confidence in Students of the Faculty of Public Health, University of Nusa Cendana - Dewi Marianty; M. Dinah Ch. Lerik; Dian Lestari Anakaka (Journal of Health and Behavioral Science, 2021)
Self-confidence is important for anyone, including students in the educational environment. Self-confidence in the sphere of education is known as academic confidence. Academic confidence plays a role in providing encouragement and motivation so that students are able to express themselves. The purpose of this study was to describe the level of academic confidence in students of the faculty of public health at Nusa Cendana University. The sampling technique used conventional sampling with the number of samples in this study as many as 333 subjects. The analysis in this study uses a central tendency analysis. Result This analysis shows that the average value of academic confidence in 333 students is 76.39, with a median or middle value of 75 and a frequently occurring value or mode of 72 and showing a standard deviation value of 0.45. The conclusion of this study is none of them are in the low category, in the medium category there are 98 (29.4%) students and in the high category there are 235 (70.6%) students.